PSYCHOSOCIAL AND PSYCHOLOGICAL FACTORS RELATED TO DELAYED RECOVERY FROM CONCUSSION IN HIGH SCHOOL STUDENTS. Issue 7 (11th March 2014) - Hutchinson, M; Comper, P; Csenge, B; Richards, D
Abstract : Background: Most of what we know about concussions has been generated from research findings with adult subjects (i.e., athletes with uncomplicated, first concussions achieve full recovery within 7 to 14 days). Emerging research suggests that younger athletes may take longer to recover from concussion than their older counterparts. However, there is little evidence that quantifies the recovery-from-concussion process in younger athletes. Objective: To describe recovery time and the contribution of pre-existing psychosocial and learning disabilities in concussion recovery in a population of high school students. Design: Retrospective chart review (January 2012-June 2013) of concussions where there was a documented medical clearance date to return to sport or physical activity. Setting: Sport medicine clinic. All concussions included occurred in subjects attending an all-boys' high school. Participants: 106 sport-related concussions were identified by chart review. 84 of the charts reviewed had definitive medical clearance dates. Of these, 33 (39%) of the students were identified with at least one of the following pre-existing conditions (PEC): Anxiety, Depression, ADHD, or Learning Disability. Main outcome measurements: Days to medical clearance. Results: Students were medically cleared to return to play on average 38 days following concussion (range 4–243 days). Signiﬁcant differences were identified between the group of students with PEC and the group without PEC. Specifically, Wilcoxon Rank-Sum tests (due to non-normal distributions) identified that the PEC group had significantly longer recovery times compared to those students with PEC (P=.03). Conclusions: High school students with concussions returned to full activity well beyond the currently accepted "normal recovery" period of 7–14 days in adults. In addition, pre-existing psychosocial and/or learning disabilities resulted in significantly longer recovery times. This information is clinically useful in post-concussive recovery assessment and education of patients and the team supporting their recovery.